1997
DOI: 10.1159/000237442
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory Effects of Platinum Compounds: Correlation between Sensitizing Properties in vivo and Modulation of Receptor-Mediated Endocytosis in vitro

Abstract: The sensitizing properties of different complex salts of platinum were defined in vivo by means of the popliteal lymph node (PLN) assay in mice. Hexa- and tetrachloroplatinates were confirmed to be highly immunogenic, inducing vigorous primary immune responses in the draining PLN following single subcutaneous injections. Flow-cytometric analysis revealed a dramatic increase in the total number of cells expressing proliferating cell nuclear antigen. The majority of these cells were of the T helper phenotype (CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The worldwide production and industrial use of platinum (Pt) and its compounds have dramatically increased since the introduction of Pt‐containing automobile catalysts two decades ago ( Rosner & Merget, 1990; WHO, 1991; Schuppe et al ., 1997 ). Apart from its applications due to excellent catalytic properties, Pt is utilized in jewellery, dental alloys, thermoelectrical devices and glass industries ( WHO, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The worldwide production and industrial use of platinum (Pt) and its compounds have dramatically increased since the introduction of Pt‐containing automobile catalysts two decades ago ( Rosner & Merget, 1990; WHO, 1991; Schuppe et al ., 1997 ). Apart from its applications due to excellent catalytic properties, Pt is utilized in jewellery, dental alloys, thermoelectrical devices and glass industries ( WHO, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular mechanism underlying this exocytic process has not been studied. As far as sensitizing properties are concerned, a structure–activity relationship between different complex Pt salts was defined both in vitro and in vivo in a murine model ( Schuppe et al ., 1997 ). Therefore, two structurally and chemically different Pt compounds—sodium‐hexachloroplatinate‐(IV), Na 2 [PtCl 6 ], known as potent sensitizer, and the nonimmunogenic tetraamineplatinum‐(II)‐chloride, [Pt(NH 3 ) 4 ]Cl 2 — were selected for the experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these salts showed strong sensitizing potency in animal models. Schuppe et al demonstrated, by means of the popliteal lymph node assay in mice, that hexa and tetrachloroplatinates had the highest sensitizing potency (4).…”
mentioning
confidence: 99%
“…The symptoms include skin changes (urticaria, contact dermatitis) and respiratory disorders ranging from sneezing, shortness of breath, and cyanosis to severe asthma [2][3][4][5][6]. The sensitizing properties of different platinum salts (e.g., disodium or ammonium hexachloroplatinate) were also proved in mice by means of the Popliteal Lymph Node Assay [3,7] and the Local Lymph Node Assay [8].…”
Section: Introductionmentioning
confidence: 99%